Color Image Encryption using Random Password Seed and Linear Feed Back Shift Register - Latef, Suhad; Hassan, Najwan A; Dhannoon, Ban N (Al-Nahrain Journal of Science, 2011)
With the fast progress of electronic data exchange, information security was become more important in data storage and transmission. And because of widely use of images in industrial process, it is important to protect the confidential image data from unauthorized access. In this paper, a proposed seed was generate as a key to a Linear Feed Back Shift Register (LFBSR) which applied on the RGB color image (Bmp image) with random keys=2100. The performance of this algorithm has been implemented on two types of Bmp image, the 8-bit Bmp image (palletized image) and 24-bit Bmp image.